User Involvement in Interaction Design in the Context of Distributed Software Development: An interview study - Alves, Daniel Domingos; Matos, Ecivaldo de Souza (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
User involvement is a key element in designing and developing interactive systems. Increasingly, software projects are being conducted with geographically distributed teams. In these projects, interaction design becomes challenging as its traditional practices start to be carried out collaboratively with geographically dispersed participants. Despite this, little is known about user involvement in interaction design in distributed software development (DSD) context. In this paper, we present the results of an interview study conducted to understand how interaction design has been implemented in DSD projects. For this, semi-structured interviews were carried out with professionals with experience in DSD. The data were analyzed based on the thematic analysis method. The results of this study provide some characteristics related to user participation in DSD, such as the level of geographic dispersion and the role of users. This study also addresses the difficulties and practices in DSD projects when involving users in the design process. We conclude, therefore, that users have participated in interaction design activities in DSD projects, but the involvement of geographically distributed users is a challenge. This paper contributes to the knowledge of interaction design at the frontier of research between Human-Computer Interaction (HCI) and DSD by identifying the main characteristics, gaps, and practices related to user involvement in DSD projects.